EFEKTIVITAS MODEL PEMBELAJARAN GUIDED DISCOVERY DENGAN PENDEKATAN OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA MATERI EKOSISTEM PADA PESERTA DIDIK DI KELAS V SD GMIT 03 KALABAHI - Anelda Suryawati Karta; Imanuel Y. H. Manapa; Jon A. Lalang Yame (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study aimed to determine the effectiveness of the Guided Discovery learning model combined with the Outdoor Learning approach on science learning outcomes in ecosystem material for fifth-grade students of SD GMIT 03 Kalabahi. The study employed a quantitative approach using an experimental method. The sample consisted of 27 students. Data were collected through tests, observations, and documentation. The results showed that the implementation of the Guided Discovery model with the Outdoor Learning approach improved students’ learning outcomes. The average post-test score of the experimental class was 74.84, higher than the control class score of 72.25. Hypothesis testing indicated a positive effect on science learning outcomes. Therefore, the Guided Discovery model integrated with Outdoor Learning is effective for improving elementary students’ understanding of ecosystem concepts.